2015
DOI: 10.1080/2162402x.2015.1005460
|View full text |Cite
|
Sign up to set email alerts
|

Th22 cells increase in poor prognosis multiple myeloma and promote tumor cell growth and survival

Abstract: There is increased production of plasmacytoid dendritic cells (pDCs) in the bone marrow (BM) of multiple myeloma (MM) patients and these favor Th22 cell differentiation. Here, we found that the frequency of interleukin (IL)-22 C IL-17 ¡ IL-13 C T cells is significantly increased in peripheral blood (PB) and BM of stage III and relapsed/refractory MM patients compared with healthy donors and patients with asymptomatic or stage I/II disease. Th22 cells cloned from the BM of MM patients were CCR6 C CXCR4 C CCR4 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 55 publications
2
41
0
Order By: Relevance
“…Importantly, the percentage of Th22 cells in ISS stage III MM patients is significantly higher compared with patients with ISS stage I/II, demonstrating that in MM increased frequency of Th22 cells associates with poor prognosis. 6 In support of our findings, increased IL-22 serum levels were also recently detected in MM patients with active disease. 29 Mechanistically, we demonstrated how the Th22 prototypical cytokines IL-22 and IL-13 exert both direct and indirect tumor-promoting functions in MM.…”
Section: Th22 Cells In MMsupporting
confidence: 78%
See 4 more Smart Citations
“…Importantly, the percentage of Th22 cells in ISS stage III MM patients is significantly higher compared with patients with ISS stage I/II, demonstrating that in MM increased frequency of Th22 cells associates with poor prognosis. 6 In support of our findings, increased IL-22 serum levels were also recently detected in MM patients with active disease. 29 Mechanistically, we demonstrated how the Th22 prototypical cytokines IL-22 and IL-13 exert both direct and indirect tumor-promoting functions in MM.…”
Section: Th22 Cells In MMsupporting
confidence: 78%
“…6 We found that Th22 (i.e., IL-22 C IL-17 ¡ IL-13 C ) cells are significantly increased in peripheral blood (PB) and BM of ISS stage III and relapsed/refractory MM patients compared with healthy donors and patients with asymptomatic (i.e., MGUS and SMM) or ISS stage I/II disease. Importantly, the percentage of Th22 cells in ISS stage III MM patients is significantly higher compared with patients with ISS stage I/II, demonstrating that in MM increased frequency of Th22 cells associates with poor prognosis.…”
Section: Th22 Cells In MMmentioning
confidence: 88%
See 3 more Smart Citations